Analisis faktor - faktor yang mempengaruhi ekspor minyak kelapa sawit di Indonesia Tahun 2000-2019 - Roni Advent; Zulgani Zulgani; Nurhayani Nurhayani (e-Journal Perdagangan Industri dan Moneter, 2021)
This research aims to analyze the development and contribution of the investment labor, and GDP mining sector in the Bungo Distric, The research was using Ordinary Least Square (OLS) method. The result of this study indicates that, during the period of 2008-2017investement, labor and GDP mining sector in the Bungo Distric is experiencing developments that fluctuate, with an average of GDP mining sector in the Bungo Distric 12,7 percent an annual, investmen 29,8 percent an annual and 2,6 percent to labor. Investmen contribution in the formation of the GDP mining sector in the Bungo Distric an average 45,2 percent. From the results of the regression shows independent variables simultaneously investment and labor effect on the dependent variables. While a partial workforce affects the PDRB while investments are not over the period of 2008-2017 years. Keywords : Investment, Labor, GDP mining sector